Millets value chain for nutritional security a replicable success model from India - Dayakar Rao, B. (Benhur) (CAB International, 2016)
While there are books that look at nutritional aspects and processing of millets, this title deals with value addition through the entire chain, from producer to consumer, and demonstrates a reliable model for millets development that can be adapted to other commodities.